Strategi Think-Talk-Write (TTW) dalam Meningkatkan Kemampuan Pemecahan Masalah IPA Siswa di Madrasah Ibtidaiyah Negeri - Novianti, Ratika (SENTRI: Jurnal Riset Ilmiah, 2025)
Science learning in elementary schools is often still dominated by conventional teacher-centered methods, which result in students being less active and their learning outcomes not being optimal. One alternative learning strategy that can increase student engagement is Think-Talk-Write (TTW), which encourages students to think, discuss, and express ideas in writing. This study aims to determine the effectiveness of the TTW strategy on students’ learning outcomes in science subjects. This research employed a quantitative approach using a quasi-experimental method. The research design used was a Nonequivalent Control Group Design. The sample consisted of two classes: an experimental class applying the TTW strategy and a control class using conventional learning methods. The instrument used was a 25-item multiple-choice test that had been validated and tested for reliability. Data analysis included normality test, homogeneity test, and t-test using SPSS software. The results showed that the data were normally distributed and homogeneous, meeting the requirements for conducting a t-test. The t-test results showed a significance value of < 0.05, indicating a significant difference in learning outcomes between students using the TTW strategy and those using conventional methods. Therefore, it can be concluded that the Think-Talk-Write strategy is effective in improving science learning outcomes among elementary school students.